New luminescent tetracoordinate boron complexes: an in-depth experimental and theoretical characterisation and their application in OLEDs. Issue 17 (20th May 2021) - Paramasivam, Krishnamoorthy; Fialho, Carina B.; Cruz, Tiago F. C.; Rodrigues, Ana I.; Ferreira, Bruno; Gomes, Clara S. B.; Vila-Viçosa, Diogo; Charas, Ana; Esperança, José M. S. S.; Vieira Ferreira, Luís F.; Calhorda, Maria José; Maçanita, António L.; et al.
Abstract : New luminescent 2-iminopyrrolyl boron complexes with different BX2 moieties are extensively studied via complementary experimental and theoretical methodologies, including application in OLEDs. Abstract : A group of new tetracoordinate mononuclear 2-( N -phenylformimino)pyrrolyl boron chelates [BX2 {κ 2 N, N ′-NC4 H3 -2-C(H)N-C6 H5 }] (X = F 3 ; mesityl (2, 4, 6-trimethylphenyl, Mes) 4 ; C6 F5 5 ; X2 = 1, 1′-biphenyl-2, 2′-diyl 6 ) and the related binuclear complex [(C6 F5 )2 B{κ 2 N, N ′-NC4 H3 -2-C(H)N-C6 H4 -NC(H)-C4 H3 N-κ 2 N, N ′}B(C6 F5 )2 ] 7 were synthesised via metathetic exchange reactions of sodium 2-( N -phenylformimino)pyrrolyl with BF3 ·Et2 O (3 ), BMes2 F (4 ) and 9-chloro-9-borafluorene (6 ), whereas 5 and 7 were obtained from the acid–base reactions between the corresponding neutral ligand precursors, respectively 2-( N -phenylformimino)pyrrole (1 ) and 1, 4-(HNC4 H3 -C(H)N)2 -C6 H4 (2 ), with B(C6 F5 )2 OEt. These complexes were designed to evaluate the influence of the boron co-ligands on the molecular properties of the corresponding 2-iminopyrrolyl tetrahedral boron derivatives, particularly on luminescence. Compounds 3–7 were photophysically characterised in solution and in solid state, exhibiting blue to yellowish-green emissions and fluorescence quantum yields ( ϕ f ) up to 0.40. The exception was complex 4, which revealed full fluorescence quenching owing to a dynamic equilibrium involving the bidentate (tetracoordinate) 2-iminopyrrolyl boron complex and the corresponding monodentate (tricoordinate) species. DFT and TDDFT studies were carried out, considering the effect of solvent and also of dispersion forces, in order to elucidate the change in geometries of compounds 3–7 from the ground to the singlet excited state, to understand the dynamic equilibrium of 4, to ascribe electronic transitions, and to rationalise the observed luminescence and also the main trends of thermal stabilities. These complexes were applied in organic light-emitting diodes (OLEDs), the ones based on complex 6 showing the best performances (maximum luminance of 170 cd m −2 and electroluminescence efficiency of 0.037 cd A −1 ).